2013
DOI: 10.1021/ma4007544
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Amphiphilic Homopolymer Micelles Using Light Scattering, SANS, and Cryo-TEM

Abstract: We report the aqueous solution self-assembly of a series of poly(N-isopropylacrylamide) (PNIPAM) polymers end-functionalized with a hydrophobic sulfur-carbon-sulfur (SCS) pincer ligand. Although the hydrophobic ligand accounted for <5 wt% of the overall homopolymer mass, the polymers self-assembled into well-defined spherical micelles in aqueous solution, and these micelles are potential precursors to solution-assembled nanoreactors for small molecule catalysis applications. The micelle structural details were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 70 publications
2
49
0
Order By: Relevance
“…This can be explained using the different applied method for micelles preparation. In fact, the applied dialysis method would avoid the formation of larger aggregates as it should happen by the direct dissolution method …”
Section: Resultsmentioning
confidence: 99%
“…This can be explained using the different applied method for micelles preparation. In fact, the applied dialysis method would avoid the formation of larger aggregates as it should happen by the direct dissolution method …”
Section: Resultsmentioning
confidence: 99%
“…56 The high electron density of QD cores provides better contrast relative to polymeric/nucleic acid systems, which often are barely visible due to their hydrated nature and low electron density. 57 Many types of electron microscopy are useful for studying nanoparticle distribution in tissue samples; 6, 58 however, cryo-TEM is uniquely suited for the analysis of nanocarriers in solution prior to delivery into biological samples. This powerful technique allows for the imaging of solution-assembled nanostructures in their native environment without the need for the samples to be stained or fixed.…”
Section: Resultsmentioning
confidence: 99%
“…In order to understand why the photoisomerization of azobenzene could downshift the LCST of the 4-propoxyazobenzene-terminated PNIPAM aqueous solution, we conducted detailed experiments with the light-responsive self-assembly behavior of polymer solution by dynamic light scattering (DLS) and static light scattering (SLS) weighted size distributions of R h for the PNIPAM4 solution before UV irradiation (23 and 25 o C) and after UV irradiation (23, 23.6 and 24 o C). DLS measurements indicated that sample PNIPAM4 formed a rather broad size distribution of micelles with an average intensity-weighted size of about 17 nm, which remained stable at 23 and 25 o C. These results showed that the particles were composed of the hydrophobic core (terminated 4-propoxyazobenzene) and the hydrophilic shell (PNIPAM chains) in amphiphilic homopolymer (PNIPAM4)[68]. Due to both tran-and cisazobenzene in the initial state, these micelles contained some larger particles, which were in exist with complex morphology as revealed by the tailing peak.…”
mentioning
confidence: 84%
“…However, when the terminated azobenzene in PNIPAM was designed to propoxyazobenzene-terminated PNIPAM aqueous solution could self-assemble into nano-micelles[68], and UV irradiation induced changes to the aggregate micelles with the result of the LCST downshift[66]. Therefore, the transition temperature ofPNIPAM4 solution by measuring the transmittance could not accurately reflect the LCST of the isolated polymer chains, and it displayed the solution of the aggregates.…”
mentioning
confidence: 99%